基于UG的链轮参数化建模与重用库建立 - 李俊文; 钟奇; 陈玉莲 (Jixie chuandong)
The principle of parametric design and modeling steps of chain wheel are introduced based on UG.Using the expression function,the parametric model and reuse library of chain wheel are built.The verification result of calling the reuse library of chain wheel shows that the parametric model is correct,and it greatly improves the efficiency of product development.